THE ACCURACY OF VAGINAL MUCUS CHARACTERISTICS AS CLINICAL SIGNS IN EARLY PREGNANCY DIAGNOSIS OF DAIRY CATTLE - Suwandi, Syifa Damaianti; Supriatna, Iman; Setiadi, Mohamad Agus (Jurnal Kedokteran Hewan, 2024)
This study aims to observe the changes in the characteristics of vaginal mucus to diagnose early pregnancy in dairy cattle. The characteristics of vaginal mucus include pH value, consistency, volume, and Vaginal Electrical Resistance (VER) value to diagnose early pregnancy using a Draminski Estrous Detector. The sample used that collected in this research was 52 dairy cattle. The research method consists of taking samples and observing the characteristics of the mucus. Data analysis includes normality test, T-test and Pearson correlation. The results showed that the mucus volume of pregnant cattle was less (1.280.356 mL) than that of non-pregnant cattle (2.210.437 mL), the pH value in pregnant cattle tended to be acidic, while non-pregnant cattle were classified as neutral, and there were differences in the consistency of mucus in pregnant cattle (4.00.0), while non-pregnant cows tended to be liquid (2.60.204). The volume and consistency of vaginal mucus in pregnant and non-pregnant cattle were significantly different (P0.05). The VER value of pregnant cattle was higher (36563.2 ohms) than non-pregnant cattle (19055.3 ohms). The VER value was highly correlated (r= 0.819) with the pregnancy status of dairy cattle. Thus, VER can be used as an accurate indicator to determine the status of early pregnancy in dairy cattle.